PENGARUH PENERAPAN MODEL PEMBELAJARAN AKTIF TIPE Class Concern TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 1 TIGO NAGARI KABUPATEN PASAMAN - Ashari, Ronaldi; Mukhni, Mukhni; Anggraini, Villia (Pendidikan Matematika, 2013)
The background of this research is the low of the studentâs understanding of mathematical concepts, so that most of the studentâs get the score under Criteria Minimum Masteri (KKM), Â the students do not active a long the learning process. The purpose of this research is to sint out the studentâs learning activiti a long the application of active learning type Class Concern and to now that the studentâs understanding mathematical concept by using active learning Class Concern strategi more better than the studentâs Â understanding of mathematical concepts by using conventional learning in class eight of SMN 1 Tigo Nagari. The study of this research is experimental, by design random experiment to ward tha subject. The population of this study is studentâs of class eighth SMPN 1 Tigo Nagari that consist of six classes. The sampel take by using random sampling tecnique. The instrument of this research is the observation paper of studentâs activities and the test of understanding mathematical concept. The technique of analyzing data of this research is T-test one hide by MINITAB. Based on the analizing data, the researcer know that basth of the sampel class have normal distribution and homogeneusÂ  in Î±=0,05. Hypothesis test the researcer get P-value=0,008 smaller than Î±=0,05, so hypothesis of this peaser is acceped. So that researcer can conclude that It the students understanding of mathematical concepts by using Aktive learning type Class Concern better than students with an understanding of the mathematical concept learning in class VIII conventional SMPN 1 Tigo Nagari.